1996
DOI: 10.1523/jneurosci.16-06-02027.1996
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis in the dentate gyrus of the adult rat: age-related decrease of neuronal progenitor proliferation

Abstract: The hippocampus is one of the few areas of the rodent brain that continues to produce neurons postnatally. Neurogenesis reportedly persists in rats up to 11 months of age. Using bromodeoxyuridine (BrdU) labeling, the present study confirms that in the adult rat brain, neuronal progenitor cells divide at the border between the hilus and the granule cell layer (GCL). In adult rats, the progeny of these cells migrate into the GCL and express the neuronal markers NeuN and calbindin-D28k. However, neurogenesis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

133
2,029
14
35

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,825 publications
(2,211 citation statements)
references
References 31 publications
133
2,029
14
35
Order By: Relevance
“…We and others have demonstrated that these precursor cells divide and produce daughter cells that differentiate into granule neurons. These cells become incorporated into the gcl and express markers of mature granule neurons, including neuron specific enolase (NSE), the calcium binding protein calbindin, the NMDA receptor subunit NR1, and Neuronal Nuclei (NeuN): within 3 weeks of DNA synthesis (Cameron et al 1993a(Cameron et al , 1993bOkano et al 1993;Kuhn et al 1996). Cells produced in adulthood receive synaptic input and extend axons into the mossy fiber pathway (Kaplan and Hinds 1977;Kaplan and Bell 1984;Stanfield and Trice 1988).…”
Section: The Production Of Hippocampal Granule Neurons Continues Intomentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have demonstrated that these precursor cells divide and produce daughter cells that differentiate into granule neurons. These cells become incorporated into the gcl and express markers of mature granule neurons, including neuron specific enolase (NSE), the calcium binding protein calbindin, the NMDA receptor subunit NR1, and Neuronal Nuclei (NeuN): within 3 weeks of DNA synthesis (Cameron et al 1993a(Cameron et al , 1993bOkano et al 1993;Kuhn et al 1996). Cells produced in adulthood receive synaptic input and extend axons into the mossy fiber pathway (Kaplan and Hinds 1977;Kaplan and Bell 1984;Stanfield and Trice 1988).…”
Section: The Production Of Hippocampal Granule Neurons Continues Intomentioning
confidence: 99%
“…The majority of these cells differentiate into mature neurons . In the aged animal, however, the production of new granule neurons diminishes significantly in both the rodent and primate (Kuhn et al 1996;Gould et al 1999a).…”
Section: The Production Of Hippocampal Granule Neurons Continues Intomentioning
confidence: 99%
See 1 more Smart Citation
“…Ageing is the greatest negative regulator of hippocampal neurogenesis (Kuhn et al, 1996), and adult neurogenesis may be required for hippocampal-dependent learning and memory (Zhao et al, 2008). Increased neurogenesis in rodents is seen following ischaemia (Takagi et al, 1999), stroke (Darsalia et al, 2005) and after seizures (Parent et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1990s, neural stem cells (NSCs) were successfully isolated from mammalian brains (Reynolds and Weiss, 1992). Shortly thereafter, by means of powerful new markers for dividing cells, such as BrdU (Kuhn et al, 1996), NSCs were eventually determined to be largely focused in two regions in the adult brain, the subgranular zone (SGZ) of the dentate gyrus of the hippocampus and the subventricular zone (SVZ) of the forebrain. All these cells are characterized by the capabilities of self-renewing and producing neurons and glial cells through asymmetric division.…”
Section: Introductionmentioning
confidence: 99%